English Romantic theatre during the Peninsular War - Valladares, S (2010)
Between 1808 and 1814 England was committed to an expensive and bloody campaign against the French invasion of the Iberian Peninsula. The Peninsular War, as it came to be known, was initially celebrated as a war of national independence that attracted widespread support. Soon after, it was characterised by political scandal and public controversy. Literary scholars have devoted much attention to the political, social and cultural effects of the French Revolution, but have written surprisingly little about the later years of the campaign against Napoleonic France. The principle objective of this thesis is to offer the first in-depth study of English theatre during the Peninsular War. It considers the most popular plays in performance, and asks what their staging, publication, and reception history reveal about a nation’s literary tastes and its political self-awareness. Sheridan’s Pizarro, a play about the Spanish conquest of Peru, was one of the most successful plays on the Romantic stage. A close analysis of this play considers its popularity between 1799 and 1815, and what it suggests about the flexibility of the contemporary repertoire system. Audiences’ ability to ascribe topical inflections to old plays helps explain the demand for Shakespeare and the bard’s political import to wartime audiences. This thesis explores the London patent stages and popular minor theatres, where programmes were restricted to song, dance, and spectacle. It also offers a case study of provincial theatre in Bristol, underscoring the significant limitations in assumptions that the metropolitan stage was representative of national trends. Archival research on the London and Bristol stages has been crucial to this study, which is based on an examination of playbills, memoranda, letters, playtexts, and prints. The newsprint and cartoons discussed offer an important political and historical framework, suggestive of the cultural expectations likely to have influenced contemporary playgoers.